Node Localization Technology of Wireless Sensor Network Based on RSSI Algorithm - Zhang, Hanqing; Li, Haitao (International Journal of Online and Biomedical Engineering (iJOE), 2016)
Wireless sensor network, as one of the system compositions of the Internet of Things, is an important carrier of the efficient use of rural resources. An accurate localization algorithm is of great significance to the complete coverage of the farmland monitoring area and to ensure the connectivity of the whole network. This paper carries out an experiment based on the signal intensities of network nodes of wireless sensor in different farmland environments having crops or not at different placing heights and relative distances. In the research, an analysis is made on the attenuation relationship between the RSSI values and the distance and height between nodes. Besides, multiple linear regression methods are used to fit the propagation model of wireless signal. Then, a distance-measuring experiment is carried out according to the model, and finally the localization of unknown nodes is realized based on Gauss mixed algorithm. Average error of the experiment is 1.02m, indicating good experimental results.